2016
DOI: 10.1016/j.addbeh.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Friends in low places: The impact of locations and companions on 21st birthday drinking

Abstract: The present research examined how various locations and companions were associated with hazardous drinking during 21st birthday celebrations. The sample included 912 college students (57% female) who completed an online survey to examine 21st birthday drinking. Locations included bars, friends’ houses, restaurants, outdoor barbecues, homes, parents’ homes, Fraternity/Sorority houses, and other. Companions included friends, family members, casual acquaintances, roommates, significant others, Fraternity/Sorority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…Surveys of natural drinking groups before and after visiting drinking establishments have shown that higher status members drink the most in heavy drinking groups, and encourage the most consumption by other members [53]. In high risk alcohol-related contexts (i.e., 21st birthday celebrations), where excessive drinking is heavily encouraged by most of the people present, romantic partners stand out as a unique protective influence [54]. These findings suggest multiple potentially fruitful avenues to pursue with respect to innovative intervention strategies by considering the roles and dynamics of individuals in personal drinking networks.…”
Section: Future Directions For Social Network Interventionsmentioning
confidence: 99%
“…Surveys of natural drinking groups before and after visiting drinking establishments have shown that higher status members drink the most in heavy drinking groups, and encourage the most consumption by other members [53]. In high risk alcohol-related contexts (i.e., 21st birthday celebrations), where excessive drinking is heavily encouraged by most of the people present, romantic partners stand out as a unique protective influence [54]. These findings suggest multiple potentially fruitful avenues to pursue with respect to innovative intervention strategies by considering the roles and dynamics of individuals in personal drinking networks.…”
Section: Future Directions For Social Network Interventionsmentioning
confidence: 99%
“…For example, drinking with friends has been associated with more alcohol consumption and consequences than drinking with family members ( Connor et al, 2014 ). There is mixed evidence for the effects of drinking with romantic partners, with some finding it to be associated with less alcohol consumption ( Rodriguez et al, 2016 ) and others finding no association ( Keough et al, 2015 ). Solitary drinking has been consistently linked to more drinking consequences ( Keough et al, 2018 ), and this has been attributed to higher coping motives for solitary drinking ( Creswell et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a number of studies have tested the efficacy of personalized normative feedback interventions. The theoretical foundation of this type of intervention relies on the power of perceived social norms to influence behavior, which has been well-documented in the alcohol literature (e.g., Miller and Brannon, 2015;Neighbors et al, 2014;Patrick et al, 2012;Rodriguez et al, 2016;Schwinn and Schinke, 2013). When applied to student drinking interventions, the personalized normative feedback typically comprises a brief message sent out to students that describes the typical drinking behavior of their peers (Miller and Brannon, 2015;.…”
Section: Introductionmentioning
confidence: 99%